Implementing Cloud Storage with OpenStack Swift. - Kapadia, Amar (Community experience distilled., 2014)
This tutorial-based book has a step-by-step approach for each topic, ensuring it is thoroughly covered and easy to follow. If you are an IT administrator who wants to enter the world of cloud storage using OpenStack Swift, then this book is ideal for you. Whether your job is to build, manage, or use OpenStack Swift, this book is an ideal way to move your career ahead. Only basic Linux and server technology skills are expected, to take advantage of this book.